Stability in Bank Income through Fee-based Activities - Uppal, R. K. (Information Management and Business Review, 2010)
This paper is an attempt to study the trends in non-interest income which is a vital source of stability in bank income. For this, the study takes some parameters like interest and non-interest income as a percentage to total income, share of non-interest income components like exchange & brokerage, sale in investment and exchange transaction. On the basis of these parameters the study concludes that interest income is continuously declining due to deregulation in interest rates and non-interest income is rising. Among the non-interest income components, commodity exchange & brokerage witnessed a large share while exchange transaction witnessed a meager part. The paper also gives some ways and means to bring stability in the total income.